A Mixed Discontinuous Galerkin Approximation of Time Dependent Convection Diffusion Optimal Control Problem. (21st February 2017) - Xu, Qingjin; Zhou, Zhaojie
Abstract : In this paper, we investigate a mixed discontinuous Galerkin approximation of time dependent convection diffusion optimal control problem with control constraints based on the combination of a mixed finite element method for the elliptic part and a discontinuous Galerkin method for the hyperbolic part of the state equation. The control variable is approximated by variational discretization approach. A priori error estimates of the state, adjoint state, and control are derived for both semidiscrete scheme and fully discrete scheme. Numerical example is given to show the effectiveness of the numerical scheme.